Cybercriminology - Graham, Roderick (Cybercrime and digital deviance, 2024)
The focus of this chapter, cybercriminology, is the various scientific theories attempting to address why cybercrime occurs. Many such theories have already been well-established in other social science disciplines, and especially sociology and criminology. Yet, in the wake of cybercrime scholarship developing in recent years, they have been repurposed in a variety of ways. Readers should find that each theory, while distinctive enough as standalone concepts, often combine with one another in efforts to explain cybercrime behavior; the authors highlight as much later in the chapter when discussing examples like cyberbullying. Finally, while not essential to understanding the chapter's material, readers should find a cursory awareness of basic sociological and criminological precepts useful as reference.